Świat jako zadanie dla inteligenta. O dwóch wierszach Stanisława Barańczaka (Spójrzmy prawdzie w oczy, Grudzień 1976) - Zbigniew Kopeć (Przestrzenie Teorii)
The analysis in this article focusses on two of Stanisław Barańczak’s poems in the context of the writer’s biography, i.e. the fact that he was an intellectual, poet, translator and essayist, as well as an opposition activist and one of the co-founders of the Workers’ Defence Committee (Komitet Obrony Robotników). The starting point is a reference to Czesław Miłosz's essays entitled Life on the isles and Immorality of art, in which the Nobel prizewinner ponders the role of the poet in the contemporary world. The poems discussed in this article are presented as one of the possible forms through which the 20th-century ethos of the intellectual is realised.